ACCOUNT OF PRODUCTION AND SALE OF PRODUCTS IN ENTERPRISES PURPOSE AND IMPORTANCE OF ORGANIZATION - Z.F.Beknazarova; I.B.Sapayev; F.S.Jo’rayev; A.A.Jo’rayev; D.B.Bozorov; D.O.A’zamova; B.N.Abdushukurov; A.D.Begmatov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The economic freedoms created in our country create ample opportunities for entrepreneurs to engage in all activities that do not conflict with the current legislation. Subjects of private and other forms of ownership aiming at profit are necessarily engaged in some production, trade, service or other type of activity. Regardless of which of the listed types of activities, the operating enterprises must make calculations with the state regarding taxes, with buyers and customers regarding the products delivered, and with employees regarding wages. This, in turn, creates the need to organize and properly maintain an account in any enterprise.